Galskap, makt og kropp. Humor i en psykiatrisk institusjon - Braathen, Espen (Tidsskriftet Antropologi, 2019)
Humour is a complex and variable social and cultural phenomenon. This article looks at how humour is used and managed by the staff within the context of a Norwegian psychiatric institution. Theories of humour in social scientific writings, are introduced in order to situate its particular anthropological contribution. By locating humor in a psychiatric context we leam that humour is not just sheer creativity and fun, but is part of a host of social processes and cultural influences. The study’s theoretical framework views humour as a device of power, regulation and control. Foucault’s notions of power and knowledge and Gramsci’s concept of hegemony are brought to bear on the use and management of humour as part of the medico-psychiatric gaze, as well as part of hegemonic interests determined by society’s larger ideological and politico-economic structures.